Reclaiming Rhetorica : Women In The Rhetorical Tradition - Lunsford, Andrea A., 1942- (Book collections on Project MUSE., 1995)
Women's contribution to rhetoric throughout Western history, like so many other aspects of women's experience, has yet to be fully explored. In pathbreaking discussions ranging from ancient Greece, though the Middle Ages and the Renaissance, to modern times, sixteen closely coordinated essays examine how women have used language to reflect their vision of themselves and their age; how they have used traditional rhetoric and applied it to women's discourse; and how women have contributed to rhetorical theory. Language specialists, feminists, and all those interested in rhetoric, composition.